AGENT-BASED NEGOTIATION MODEL FOR PUBLIC PROCUREMENT IN BRAZIL - Gonçalo, Thomas; Morais, Danielle (International Journal of Industrial Engineering: Theory, Applications and Practice, 2019)
Brazil has specific legislation regarding public procurement, establishing rules for the Public Administration when hiring contractors. Despite clear legislation, corruption in the selection of suppliers is often noted. In order to bring more transparency to the process, as well as to minimize the possibility of corruption, the use of public e-procurement systems is growing. In this context, specifically in the Brazilian case, an agent-based negotiation model is proposed to automate the negotiation and selection of suppliers in the electronic auction modality. The model is composed of procedures to measure the utility of each proposal; generate counter-proposals through concession tactics; and to choose the most appropriate supplier, according to the utility of proposals at the end of the negotiation. A negotiation simulation was performed in an instance of the acquisition of a product by a Brazilian university. It was possible to verify the applicability of the model and evaluate the impact of the parameters in the result of the negotiation process